The prester John of the Indies : a true relation of the lands of the prester John, being the narrative of the Portuguese embassy to Ethiopia in 1520, written by Father Francisco Alvares.: a true relation of the lands of the prester John, being the narrative of the Portuguese embassy to Ethiopia in 1520, written by Father Francisco Alvares. Vol I (2017) - Alvares, Francisco
No abstract available